2023
DOI: 10.3390/md22010024
|View full text |Cite
|
Sign up to set email alerts
|

Pepsin Hydrolysate from Surimi Industry-Related Olive Flounder Head Byproducts Attenuates LPS-Induced Inflammation and Oxidative Stress in RAW 264.7 Macrophages and In Vivo Zebrafish Model

H. H. A. C. K. Jayawardhana,
N. M. Liyanage,
D. P. Nagahawatta
et al.

Abstract: Fish head byproducts derived from surimi processing contribute about 15% of the total body weight, which are beneficial to health because they contain essential nutrients. In this study, olive flounder (OF) was the target species in order to maximize the byproduct utilization. In RAW 264.7 macrophages, the seven hydrolysates from OF head byproducts were examined for their inhibitory potential against inflammation and the oxidative stress induced by lipopolysaccharides (LPS). The pepsin hydrolysate (OFH–PH) dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Therefore, it is important to investigate therapeutic approaches to treat this condition to prevent DEXA-induced muscle atrophy, introduce anti-muscle atrophy compounds to prevent important clinical implications, and investigate anti-muscle atrophy drugs or foods to treat these conditions effectively. Numerous studies have shown that enzyme-assisted extraction methods provide outstanding outcomes, including efficient extraction of bioactive compounds with greater extraction yields and protein content, which are highly recognized for superlative muscle growth [ 6 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to investigate therapeutic approaches to treat this condition to prevent DEXA-induced muscle atrophy, introduce anti-muscle atrophy compounds to prevent important clinical implications, and investigate anti-muscle atrophy drugs or foods to treat these conditions effectively. Numerous studies have shown that enzyme-assisted extraction methods provide outstanding outcomes, including efficient extraction of bioactive compounds with greater extraction yields and protein content, which are highly recognized for superlative muscle growth [ 6 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%